A novel, new generation drill coating for osteotomy site preparation - Pooja P Wadkar; Suraj Khalap; Devanand Shetty; Abhishek Gupta; Arvind Shetty; Suyog Dharmadhikari (Wolters Kluwer Medknow Publications, 2019)
Background: Implant success and survival rate ranges from 93% to 97%; however, failures are not very uncommon. These failures can be caused due to a variety of reasons out of which increased heat during drilling of osteotomies is a major contributor.Aim: The aim of this study was to develop a new generation diamond-coated drill and compare the thermal changes between commercially available drills and the experimental diamond coated drill during implant site preparation in artificial bone. Material and Methods: Three types of drills were selected for the study; Group A (Carbide), Group B (Stainless Steel), and Group C (Experimental). A total of 60 implant site preparations were performed with all the drills in artificial bone using a surgical unit linked to a testing device, in order to standardize implant drilling procedures. Bone temperature variations were recorded when drilling at a depth of 10 mm. A constant irrigation of 50 ml/minute and drilling speed of 800 r.p.m. was maintained. Results: The mean temperature of Group A, Group B, and Group C was 35.57°C, 36.83°C and 34.23°C, respectively. The results were assessed and statistically analyzed using ANOVA test and post hoc Bonferroni test. Statistically significant higher temperatures were obtained with stainless steel drill and carbide drill when compared with the experimental diamond coated drill. (P = 0.000). Conclusions: Diamond coated osteotomy drills have shown promising results in reducing heat generation at the osteotomy. Further studies need to be conducted to maximize the potential use of diamond as components of drills in implant dentistry.